Negative ion ceramic glaze and preparation method thereof

By adding nano-alumina, nano-zirconia, nano-boron oxide and anti-cracking substances to the ceramic glaze, combined with negative ion initiator and water, the problem of negative ion ceramic glaze is easily cracked at low temperatures, and the cracking resistance is significantly improved , ensuring the normal use of glaze.

CN119241072APending Publication Date: 2025-01-03YIXING YIAN CERAMICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411178676.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-03
Patent Text Reader

Abstract

The invention discloses negative ion ceramic glaze and a preparation method thereof. The negative ion ceramic glaze is prepared from the following raw materials in parts by weight: 10 to 20 parts of quartz, 20 to 30 parts of feldspar, 30 to 40 parts of clay, 10 to 20 parts of oxide, 2 to 4 parts of nano aluminum oxide, 6 to 8 parts of nano zirconium oxide, 5 to 7 parts of nano boron oxide, 31 to 41 parts of anti-cracking substance, 1 to 3 parts of negative ion initiator and 30 to 40 parts of negative ion water. According to the invention, the ceramic glaze forms the anion ceramic glaze through the anion initiator and the anion water, the antifouling and antibacterial effects of the anion ceramic glaze can be improved through the arrangement of the nano aluminum oxide, the nano zirconium oxide and the nano boron oxide, and the anti-cracking effect of the anion ceramic glaze can be improved through the anti-freezing agent, the starch plastic, the phosphate and the silver-loaded nano zinc oxide in the anti-cracking substance. The anti-cracking effect of the ceramic glaze is improved, a user does not crack when the ceramic glaze is prepared, and the anti-cracking effect of the ceramic glaze can be improved, so that normal use of the user is ensured, and the phenomenon that the ceramic glaze cracks when being prepared into ceramics is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic glazes, in particular to a negative ion ceramic glaze and a preparation method thereof. Background Art

[0002] The building sanitary ceramics industry pays great attention to the use of advanced glaze technology. A large number of highly professional ceramic glaze, ceramic frit and colorant companies have emerged in China. The glazes used in building sanitary ceramic products are becoming more and more diverse. The categories and uses of glaze products used by most ceramic companies can be roughly classified as follows: 1. Lead glaze and lead-free glaze; 2. Raw material glaze and frit glaze; 3. Glaze for single firing or double firing; 4. Glaze for tiles, tableware, sanitary ceramics and electrical porcelain; 5. Glaze, spray glaze and pour glaze divided by glazing method; 6. High temperature glaze and low temperature glaze; 7. High expansion glaze and low expansion glaze; 8. Firing atmosphere oxidizing flame, neutral flame and reducing flame; 9. Color glaze and colorless glaze; 10. Transparent glaze and opaque glaze; 11. Glossy glaze, matte glaze, semi-matte glaze or patterned glaze, etc.

[0003] There are many kinds of ceramic glazes, and negative ion ceramic glaze is one of them. For example, a Chinese patent discloses a ceramic glaze capable of releasing negative ions and a preparation method thereof, with the publication (announcement) number: CN116655244A, wherein the ceramic glaze comprises the following components by weight: 7-9 parts by weight of kaolin, 1-3 parts by weight of negative ion agent, 15-25 parts by weight of potassium feldspar, 6-9 parts by weight of quartz, and 3-5 parts by weight of modified porous mixture. The ceramic glaze of the present invention is applied to the surface of ceramic tiles, and the added negative ion initiator can efficiently trigger the glaze to release negative ions, while the modified porous mixture has the function of absorbing harmful gases and enhancing negative ion reactions. The two are compounded to effectively purify the air and improve the air quality, which is in line with the current environmental protection concept. The above patent can efficiently trigger the glaze to release negative ions when used, but the negative ion ceramic glaze is easy to crack under low temperature conditions, resulting in the user's easy cracking phenomenon when the ceramic glaze is made, and the anti-cracking effect of the ceramic glaze cannot be improved, thereby affecting the normal use of the user. Summary of the invention

[0004] In order to solve the problems raised in the above background technology, the purpose of the present invention is to provide a negative ion ceramic glaze and a preparation method thereof, which has the advantage of improving the anti-cracking effect of the ceramic glaze, and solves the problem that the negative ion ceramic glaze cannot improve the anti-cracking effect of the ceramic glaze.

[0005] To achieve the above object, the present invention provides the following technical solution: a negative ion ceramic glaze, comprising the following raw materials in proportions by weight:

[0006] 10-20 parts of quartz, 20-30 parts of feldspar, 30-40 parts of clay, 10-20 parts of oxide, 2-4 parts of nano-alumina, 6-8 parts of nano-zirconia, 5-7 parts of nano-boron oxide, 31-41 parts of anti-cracking material, 1-3 parts of negative ion initiator and 30-40 parts of negative ion water.

[0007] As a preferred embodiment of the present invention, the oxide comprises a mixture of lead oxide, aluminum oxide and silicon dioxide in a percentage of 64%: 3%: 33%.

[0008] As a preferred embodiment of the present invention, the anti-cracking substance is antifreeze, starch plastic, phosphate and silver-loaded nano zinc oxide, and the weight ratio is: 6-8 parts of antifreeze, 7-9 parts of starch plastic, 4-6 parts of phosphate and 8-10 parts of silver-loaded nano zinc oxide.

[0009] The method for preparing the negative ion ceramic glaze of the present invention comprises the following preparation steps:

[0010] Crushing and grinding steps: the user sequentially pours 10-20 parts of quartz, 20-30 parts of feldspar, 30-40 parts of clay, 10-20 parts of oxide, 2-4 parts of nano-alumina, 6-8 parts of nano-zirconia, 5-7 parts of nano-boria and 31-41 parts of anti-cracking material into the crusher for crushing, and the crushing time is 20-30 minutes, and then pours the crushed quartz 10-20 parts, feldspar 20-30 parts, clay 30-40 parts, oxide 10-20 parts, nano-alumina 2-4 parts, nano-zirconia 6-8 parts, nano-boria 5-7 parts and anti-cracking material 31-41 parts into the grinding device, grinds the quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boria and anti-cracking material, and the grinding time is: 40-50 minutes to form powder;

[0011] Mixing steps: first, pour 10-20 parts of quartz, 20-30 parts of feldspar and 30-40 parts of clay into the mixer, and stir for 10-20 minutes. Then, pour 10-20 parts of oxide, 2-4 parts of nano-alumina and 6-8 parts of nano-zirconia into the mixer, and stir for 10-15 minutes. Then, pour 5-7 parts of nano-boron oxide and 31-41 parts of anti-cracking material into the mixer and stir for 30-40 minutes. The quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boron oxide and anti-cracking material are fully mixed to form a mixture one. Then, pour 1-3 parts of negative ion initiator and 30-40 parts of negative ion water into the mixer, and stir the negative ion initiator and negative ion water into the mixture one through the mixer. The stirring time is 30-40 minutes to form a mixture two:

[0012] Forming and storage steps: pour the mixture 2 into the interior of the dryer, dry the mixture 2 through the dryer, the drying temperature is: 60-70°C, the drying time is: 50-60min, and then form a negative ion ceramic glaze, and then grind the negative ion ceramic glaze through a grinder to form a negative ion ceramic glaze powder, and store the negative ion ceramic glaze powder through a storage tank.

[0013] As a preferred embodiment of the present invention, in the crushing and grinding step, a cover plate is movably connected to the top of the crusher, and the top of the crusher is sealed by the cover plate to prevent flying dust generated inside the crusher from floating out from the top of the crusher.

[0014] As preferred embodiment of the present invention, in the crushing and grinding step, a filter is provided at the bottom of the grinding device, through which the ground quartz, feldspar, clay, oxides, nano-alumina, nano-zirconia, nano-boria and anti-cracking substances are filtered to prevent granular quartz, feldspar, clay, oxides, nano-alumina, nano-zirconia, nano-boria and anti-cracking substances from entering the interior of the storage box.

[0015] As a preferred embodiment of the present invention, in the mixing step, a glass is fixedly installed on the front of the mixer, and the user can observe the internal mixing conditions through the glass.

[0016] As a preferred embodiment of the present invention, in the molding and storage step, a temperature sensor is fixedly installed inside the dryer, and the temperature inside the dryer is displayed by the temperature sensor, so that the user can understand the internal temperature.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The present invention forms a negative ion ceramic glaze by using 1-3 parts of a negative ion initiator and 30-40 parts of negative ion water. The antifouling and antibacterial effects of the negative ion ceramic glaze can be improved by setting nano-alumina, nano-zirconium oxide and nano-boron oxide. The anti-cracking effect of the ceramic glaze is improved by using antifreeze, starch plastic, phosphate and silver-loaded nano-zinc oxide in the anti-cracking substances. The user will not experience cracking when the ceramic glaze is made, and the anti-cracking effect of the ceramic glaze can be improved, thereby ensuring the normal use of the user and avoiding the ceramic glaze from cracking when the ceramic glaze is made into ceramics. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Embodiment 1

[0021] Negative ion ceramic glaze, including the following raw materials in proportions by weight:

[0022] 10 parts of quartz, 20 parts of feldspar, 30 parts of clay, 10 parts of oxides, 2 parts of nano-alumina, 6 parts of nano-zirconium oxide, 5 parts of nano-boric oxide, 31 parts of anti-cracking substances, 1 part of negative ion initiator and 30 parts of negative ion water.

[0023] The method for preparing negative ion ceramic glaze is characterized by comprising the following preparation steps:

[0024] Crushing and grinding steps: the user sequentially pours 10 parts of quartz, 20 parts of feldspar, 30 parts of clay, 10 parts of oxide, 2 parts of nano-alumina, 6 parts of nano-zirconia, 5 parts of nano-boria and 31 parts of anti-cracking material into the grinder for crushing, and the crushing time is 20 minutes, and then pours the crushed quartz 10 parts, 20 parts of feldspar, 30 parts of clay, 10 parts of oxide, 2 parts of nano-alumina, 6 parts of nano-zirconia, 5 parts of nano-boria and 31 parts of anti-cracking material into the grinding device, grinds the quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boria and anti-cracking material, and the grinding time is: 40 minutes to form powder;

[0025] Mixing steps: first, pour 10 parts of quartz, 20 parts of feldspar and 30 parts of clay into the mixer, and stir for 10 minutes. Then, pour 10 parts of oxide, 2 parts of nano-alumina and 6 parts of nano-zirconia into the mixer, and stir for 10 minutes. Then, pour 5 parts of nano-boron oxide and 31 parts of anti-cracking material into the mixer and stir for 30 minutes. The quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boron oxide and anti-cracking material are fully mixed to form mixture 1. Then, pour 1 part of negative ion initiator and 30 parts of negative ion water into the mixer, and stir the negative ion initiator and negative ion water into mixture 1 through the mixer. The stirring time is 30 minutes to form mixture 2:

[0026] Forming and storage steps: pour the mixture 2 into the interior of the dryer, dry the mixture 2 through the dryer, the drying temperature is: 60°C, the drying time is: 50min, and then form a negative ion ceramic glaze, and then grind the negative ion ceramic glaze through a grinder to form a negative ion ceramic glaze powder, and store the negative ion ceramic glaze powder through a storage tank.

[0027] Embodiment 2

[0028] Negative ion ceramic glaze, including the following raw materials in proportions by weight:

[0029] 15 parts of quartz, 25 parts of feldspar, 35 parts of clay, 15 parts of oxide, 3 parts of nano-alumina, 7 parts of nano-zirconium oxide, 6 parts of nano-boron oxide, 36 parts of anti-cracking material, 2 parts of negative ion initiator and 35 parts of negative ion water.

[0030] The method for preparing negative ion ceramic glaze is characterized by comprising the following preparation steps:

[0031] Crushing and grinding steps: the user sequentially pours 15 parts of quartz, 25 parts of feldspar, 35 parts of clay, 15 parts of oxide, 3 parts of nano-alumina, 7 parts of nano-zirconia, 6 parts of nano-boria and 36 parts of anti-cracking material into the grinder for crushing, and the crushing time is 25 minutes, and then pours the crushed quartz 15 parts, 25 parts of feldspar, 35 parts of clay, 15 parts of oxide, 3 parts of nano-alumina, 7 parts of nano-zirconia, 6 parts of nano-boria and 36 parts of anti-cracking material into the grinding device, grinds the quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boria and anti-cracking material, and the grinding time is: 45 minutes to form powder;

[0032] Mixing steps: first, pour 15 parts of quartz, 25 parts of feldspar and 35 parts of clay into the mixer, and stir for 15 minutes. Then, pour 15 parts of oxide, 3 parts of nano-alumina and 7 parts of nano-zirconia into the mixer, and stir for 13 minutes. Then, pour 6 parts of nano-boria and 36 parts of anti-cracking material into the mixer and stir for 35 minutes. The quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boria and anti-cracking material are fully mixed to form mixture 1. Then, pour 2 parts of negative ion initiator and 35 parts of negative ion water into the mixer, and stir the negative ion initiator and negative ion water into mixture 1 through the mixer. The stirring time is 35 minutes to form mixture 2:

[0033] Forming and storage steps: pour the mixture 2 into the interior of the dryer, dry the mixture 2 through the dryer, the drying temperature is: 65°C, the drying time is: 55min, and then form a negative ion ceramic glaze, and then grind the negative ion ceramic glaze through a grinder to form a negative ion ceramic glaze powder, and store the negative ion ceramic glaze powder through a storage tank.

[0034] Embodiment 3

[0035] Negative ion ceramic glaze, including the following raw materials in proportions by weight:

[0036] 20 parts of quartz, 30 parts of feldspar, 40 parts of clay, 20 parts of oxide, 4 parts of nano-alumina, 8 parts of nano-zirconium oxide, 7 parts of nano-boric oxide, 41 parts of anti-cracking material, 3 parts of negative ion initiator and 40 parts of negative ion water.

[0037] The method for preparing negative ion ceramic glaze is characterized by comprising the following preparation steps:

[0038] Crushing and grinding steps: the user sequentially pours 20 parts of quartz, 30 parts of feldspar, 40 parts of clay, 20 parts of oxide, 4 parts of nano-alumina, 8 parts of nano-zirconia, 7 parts of nano-boria and 41 parts of anti-cracking material into the grinder for crushing, and the crushing time is 30 minutes, and then pours the crushed quartz 20 parts, 30 parts of feldspar, 40 parts of clay, 20 parts of oxide, 4 parts of nano-alumina, 8 parts of nano-zirconia, 7 parts of nano-boria and 41 parts of anti-cracking material into the grinding device, grinds the quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boria and anti-cracking material, and the grinding time is: 50 minutes to form powder;

[0039] Mixing steps: first, pour 20 parts of quartz, 30 parts of feldspar and 40 parts of clay into the mixer, and stir for 20 minutes. Then, pour 20 parts of oxide, 4 parts of nano-alumina and 8 parts of nano-zirconia into the mixer, and stir for 15 minutes. Then, pour 7 parts of nano-boron oxide and 41 parts of anti-cracking material into the mixer and stir for 40 minutes. The quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boron oxide and anti-cracking material are fully mixed to form mixture 1. Then, pour 3 parts of negative ion initiator and 40 parts of negative ion water into the mixer, and stir the negative ion initiator and negative ion water into the mixer. The negative ion initiator and negative ion water are stirred into the mixture 1 by the mixer for 40 minutes to form mixture 2:

[0040] Forming and storage steps: pour the mixture 2 into the interior of the dryer, dry the mixture 2 through the dryer, the drying temperature is: 70°C, the drying time is: 60min, and then form a negative ion ceramic glaze, and then grind the negative ion ceramic glaze through a grinder to form a negative ion ceramic glaze powder, and store the negative ion ceramic glaze powder through a storage tank.

[0041] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0042] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Negative ion ceramic glaze, characterized in that: The invention comprises the following raw materials in proportions by weight: 10-20 parts of quartz, 20-30 parts of feldspar, 30-40 parts of clay, 10-20 parts of oxide, 2-4 parts of nano-alumina, 6-8 parts of nano-zirconia, 5-7 parts of nano-boron oxide, 31-41 parts of anti-cracking material, 1-3 parts of negative ion initiator and 30-40 parts of negative ion water.

2. The negative ion ceramic glaze according to claim 1, characterized in that: The oxides include a mixture of lead oxide, aluminum oxide and silicon dioxide in a percentage of 64%: 3%: 33%.

3. The negative ion ceramic glaze according to claim 1, characterized in that: The anti-cracking substances are antifreeze, starch plastic, phosphate and silver-loaded nano zinc oxide, and the weight ratio is: 6-8 parts of antifreeze, 7-9 parts of starch plastic, 4-6 parts of phosphate and 8-10 parts of silver-loaded nano zinc oxide.

4. The method for preparing anion ceramic glaze according to claim 1, characterized in that: The method comprises the following preparation steps: Crushing and grinding steps: the user sequentially pours 10-20 parts of quartz, 20-30 parts of feldspar, 30-40 parts of clay, 10-20 parts of oxide, 2-4 parts of nano-alumina, 6-8 parts of nano-zirconia, 5-7 parts of nano-boria and 31-41 parts of anti-cracking material into the crusher for crushing, and the crushing time is 20-30 minutes, and then pours the crushed quartz 10-20 parts, feldspar 20-30 parts, clay 30-40 parts, oxide 10-20 parts, nano-alumina 2-4 parts, nano-zirconia 6-8 parts, nano-boria 5-7 parts and anti-cracking material 31-41 parts into the grinding device, grinds the quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boria and anti-cracking material, and the grinding time is: 40-50 minutes to form powder; Mixing steps: first, pour 10-20 parts of quartz, 20-30 parts of feldspar and 30-40 parts of clay into the mixer, and stir for 10-20 minutes. Then, pour 10-20 parts of oxide, 2-4 parts of nano-alumina and 6-8 parts of nano-zirconia into the mixer, and stir for 10-15 minutes. Then, pour 5-7 parts of nano-boron oxide and 31-41 parts of anti-cracking material into the mixer and stir for 30-40 minutes. The quartz, feldspar, clay, oxide, nano-alumina, nano-zirconia, nano-boron oxide and anti-cracking material are fully mixed to form a mixture one. Then, pour 1-3 parts of negative ion initiator and 30-40 parts of negative ion water into the mixer, and stir the negative ion initiator and negative ion water into the mixture one through the mixer. The stirring time is 30-40 minutes to form a mixture two: Forming and storage steps: pour the mixture 2 into the interior of the dryer, dry the mixture 2 through the dryer, the drying temperature is: 60-70°C, the drying time is: 50-60min, and then form a negative ion ceramic glaze, and then grind the negative ion ceramic glaze through a grinder to form a negative ion ceramic glaze powder, and store the negative ion ceramic glaze powder through a storage tank.

5. The method for preparing anion ceramic glaze according to claim 1, characterized in that: In the crushing and grinding step, a cover plate is movably connected to the top of the crusher, and the top of the crusher is sealed by the cover plate to prevent flying dust generated inside the crusher from floating out from the top of the crusher.

6. The method for preparing anion ceramic glaze according to claim 1, characterized in that: In the crushing and grinding step, a filter is provided at the bottom of the grinding device, through which the ground quartz, feldspar, clay, oxides, nano-alumina, nano-zirconia, nano-boria and anti-cracking substances are filtered to prevent granular quartz, feldspar, clay, oxides, nano-alumina, nano-zirconia, nano-boria and anti-cracking substances from entering the interior of the storage box.

7. The method for preparing anion ceramic glaze according to claim 1, characterized in that: In the mixing step, a glass is fixedly installed on the front of the mixer, and the user can observe the internal mixing situation through the glass.

8. The method for preparing anion ceramic glaze according to claim 1, characterized in that: In the molding and storage step, a temperature sensor is fixedly installed inside the dryer, and the temperature inside the dryer is displayed by the temperature sensor, so that the user can understand the internal temperature.